Factors Impacting Progress of Students’ Educational Efficiency: a Case of Secondary School Level: Exploring the Relationship between Factors and Educational Efficiency (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This study was conducted to examine different factorsinfluencing the academic performance of secondary school students in ametropolitan city of India. The respondents for this study were 10th gradestudents (300 male & 300 female). A survey was conducted by using aquestionnaire for information gathering about different factors relating toacademic performance of students. The academic performance was gauged by theresult of their 9th grade annual examination. Standard t-test and ANOVA wereapplied to investigate the effect of different factors on students’achievement. The results of the study revealed that socio-economic status (SES)and parents’ education have a significant effect on students’ overall academicachievement as well as achievement in the subjects of Mathematics and English.The high and average socio-economic level affects the performance more than thelower level. It is very interesting that parents’ education means more thantheir occupation in relation to their children’s academic performance atschool. It was found that girls perform better than the male students.